Edge detection techniques for iris recognition system - Tania, U. T.; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (2013)
Nowaday s security and authentication are the major part s of our daily life. Iris is one of the most reliable organ or part of human body which can be used for identification and authentication purpose. To develop an iris authentication algorithm for personal identification, this paper examines two edge detection techniques for iris recognition system. Between the Sobel and the Canny edge detection techniques, the experimental result shows that the Canny’s technique has better ability to detect poi nts in a digital image where image gray level changes even at slow rate.